(untitled) (Research, Society and Development, 2022)
Highways are the most used modal for the transportation of cargo and people in Brazil. However, there is usually no availability of soils that meet pavement design criteria, emphasizing the need for soil stabilization techniques for material adjustments within the desired specifications. Therefore, this work aimed to evaluate the behavior of a well-graded silty sand (SM-SW) from the city of Natal/RN, whose characteristics are unsatisfactory for paving. It was stabilized with fast-breaking asphalt emulsion (RR-2C). California Bearing Ratio (CBR) and Dynamic Cone Penetrometer (DCP) tests were performed in three emulsion contents (3%, 5%, and 7%) under three conditions: without curing and without immersion; without curing and with immersion; and with 7 days cure and immersion. The results indicate a reduction in bearing capacity after mixing, even though the correlations between CBR and DCP have presented more adequate adjustments and improved coefficients of determination (R²), with values superior to 0.80. Besides, after the curing process, there was an increase in the CBR values, but the emulsion has still proven to be low effective in stabilizing the soil for use as base and sub-base of a pavement.